Disparities in melanoma incidence and mortality in rural versus urban Michigan. Issue 2 (14th October 2022) - Shellenberger, Richard A.; Johnson, Timothy M.; Fayyaz, Fatima; Swamy, Bhanu; Albright, Jeremy; Geller, Alan C.
Abstract: Introduction: We sought to identifying the possible existence of disparities between rural and urban residents of Michigan for the incidence by stage of disease and disease‐specific mortality for cutaneous melanoma (CM). Methods: Incidence rates for stage of disease and disease‐specific mortality of cutaneous melanoma were calculated and controlled for gender, age, and area of residence from January 1, 2014, to December 31, 2018, from data collected form the Michigan Department of Health and Human Services and the Centers for Disease Control and Prevention. Results: The incidence rates for CM were significantly higher in rural Michigan counties, from 2014–2018, for all patients, both age groups, both genders and all stages. Melanoma‐specific mortality rates were also significantly higher for all patients, both age groups and both genders in rural Michigan counties. Using logistic regression analysis, while controlling for age and gender, rural Michigan counties continued to have a higher melanoma‐specific morality rate during our study period (OR = 1.491; 95% CI, 1.27–1.74; p  = <.001). Conclusion: We found significant disparities in the incidence rates and disease specific mortality for cutaneous melanoma in rural compared to urban Michigan from 2014–2018.